Multi-criteria location identification for wind/solar based hydrogen generation: The case of capital cities of a developing country - Rezaei, Mostafa; Khalilpour, Kaveh R.; Jahangiri, Mehdi (International journal of hydrogen energy, 2020)
The identification of site location is one of the critical tasks in developing or expanding any supply chain system including the construction of renewable power generation plants. The accurate identification of a plant site can considerably reduce unforeseen risks and costs and also raise productivity and efficacy. As such, this study sought to thoroughly evaluate all capital cities of a developing country for the establishment of a hybrid wind/solar power plant to produce hydrogen while considering the most influential and conflicting criteria. For this, 14 criteria including daily solar radiation, wind power density, clearness index, altitude, population, average sunny hours in a year, unemployment rate, average air temperature, average air humidity, average yearly precipitation, natural disasters, the distance between the site and the main road, average dusty days per year, and land price constituted the set of vital factors. To prioritize alternatives, a Fuzzy Multi-Criteria Decision Making approach named FVIKOR (Fuzzy Multi-Criteria Optimization and Compromise Solution) was used. The results indicated that among 31 capital cities, the city of Yazd with a wind power density of 309.5 W/m2 and daily solar radiation of 5.4 kWh/m2 would be the best location for the purpose of this study. To validate the findings, FTOPSIS (Fuzzy Technique for Order Preference by Similarity to Ideal Solution) method was utilized and it also ranked Yazd as the first option. Then, a sensitivity analysis was conducted to discern the behavior of each criterion and their impact on the ranking of the cities. Finally, for hydrogen generation, an autonomous hybrid wind/solar system was techno-economically assessed using HOMER software. According to the analysis outcome, the proposed system showed a payback period of 7 years with levelized cost of 4.75 $/kg for hydrogen. •Utilizing Fuzzy VIKOR for accurate location planning of a stand-alone hybrid wind/solar site.•Proposing crucial and conflicting criteria for the process of prioritization.•Validating the results of ranking via FTOPSIS.•Investigating all 31 capital cities of Iran.